We Need to Change. Ideas of Growth and Development in a Time of Crisis of Fossil Energy and Capitalism - Domazet, Mladen (Array, 2014)
The purpose of this paper is to lay the groundwork, and provoke others to dig it up, for the holistic understanding of the economic hopes and geophysical drivers behind the themes of green economy and degrowth. It first fights for the voice in which to frame the warning of global civilizational collapse, its physical and historic drivers and experiential instantiations. The paper surveys the opinions of scholars from environmental science, biology, history, leftist social theory and economics addressing the notion that the global civilisation as we know it is facing a collapse of human societies and practices sustaining it. Whilst there are historical narratives that evoke hope for a technological overcoming of this problem, in the text I endeavour to show how such a gamble is based on ontological confusion about the fundamental elements of the modern developmental success. The paper elucidates how the key collapse-mitigating model is not a matter of small life-style changes reliant on technological transcence of physical constraints, but a matter of serious social restructuring that would replace the missing technological fix. But for that to become democratically acceptable, the societies must renegotiate the indicators and definitions of what wellbeing consists in, whilst humanity must redefine what its endurance is to consist of, not hope for the miracle of green economy.